Paternal dominance of trans-eQTL influences gene expression patterns in maize hybrids - Swanson-Wagner, Ruth A; DeCook, Rhonda; Jia, Yi; Bancroft, Tim; Ji, Tieming; Zhao, Xuefeng; Nettleton, Dan; Schnable, Patrick S (Science (American Association for the Advancement of Science), 2009)
Heterosis refers to the superior performance of hybrid progeny relative to their inbred parents, but the mechanisms responsible are unknown. Hybrids between the maize inbred lines B73 and Mo17 exhibit heterosis regardless of cross direction. These reciprocal hybrids differ from each other phenotypically, and 30 to 50% of their genes are differentially expressed. We identified approximately 4000 expression quantitative trait loci (eQTL) that allowed us to identify markers linked to variation in expression. We found that over three-quarters of these eQTL act in trans (78%) and that 86% of these differentially regulate transcript accumulation in a manner consistent with gene expression in the hybrid being regulated exclusively by the paternally transmitted allele. This result suggests that widespread imprinting contributes to the regulation of gene expression in maize hybrids.